To the question of estimation of teeth interaction conditions in bevel gear on contact parameters and tribotechnical characteristics. Part 2. Helical gear - Чернець, М.В; Чернець, Ю.М. (Problems of Tribology, 2016)
In the paper are presented the results of estimation of maximum contact pressures, wear and durability of bevel helical gear taking into account parity of teeth engagement, change of their involute profiles curvature in the result of wear and angular correction of engagement. Calculation of bevel gear is conducted as for the equivalent cylindrical gear according to the author’s method. The established regularities of influence of mentioned conditions of teeth interaction in front and in-ternal cut of bevel wheels rim are presented graphically. Optimum values of correction coefficients, which provide maximum gear durability, are revealed.